Sleep disturbances and daytime fatigue: data from the Brazilian National Health Survey, 2013 - Andrea Wendt; Caroline Santos Costa; Adriana Kramer Fiala Machado; Francine Santos Costa; Rosália Garcia Neves; Thaynã Ramos Flores; Iná Santos; Fernando César Wehrmeister (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: This study aims to describe the prevalence of sleep disturbances and daytime fatigue and their association with socio-demographic and behavioral factors. Data from the Brazilian National Health Survey conducted in 2013 with 60,202 adults (≥ 18 years old) were used. The outcomes evaluated were self-reported sleep disturbances and daytime fatigue in the last two weeks. Sleep disturbance was defined as the presence of difficulty to fall asleep, frequently waking up during the night or sleeping more than usual; daytime fatigue was defined as the presence of not feeling rested and motivated during the day, feeling tired and lacking energy. Sociodemographic, lifestyle and chronic health aspects were explored as exposures for both outcomes. Prevalence of sleep disturbances and daytime fatigue were 14.9% (14.4-15.4) and 11.9% (11.4-12.3), respectively. Both outcomes were more common in women, older people, people with no formal education, smokers and among physically inactive individuals. The association with education was inverse (the highest the level of education the lower the prevalence ratio - PR - of sleep disturbances and daytime fatigue; adjusted p-value for trend < 0.001). Prevalence of sleep disturbances combined with daytime fatigue was 6.7% (6.4-7.1) and was about 6 times higher among those with three or more chronic health disturbances (PR = 6.2; 95%CI: 5.3-7.2). Strategies to decrease the prevalence of sleep disturbances and daytime fatigue should be encouraged and focused on chronically ill individuals that share other modifiable risk factors.